Coronavirus Disease 2019 Catheterization Laboratory Survey - Banerjee, Subhash (J Am Heart Assoc, 2020)
BACKGROUND: The coronavirus disease 2019 pandemic is expected to affect operations and lifestyles of interventional cardiologists around the world in unprecedented ways. Timely gathering of information on this topic can provide valuable insight and improve the handling of the ongoing and future pandemic outbreaks. METHODS AND RESULTS: A survey instrument developed by the authors was disseminated via e‐mail, text messaging, WhatsApp, and social media to interventional cardiologists between April 6, 2020, and April 11, 2020. A total of 509 responses were collected from 18 countries, mainly from the United States (51%) and Italy (36%). Operators reported significant decline in coronary, structural heart, and endovascular procedure volumes. Personal protective equipment was available to 95% of respondents; however FIT‐tested N95 or equivalent masks were available to only 70%, and 74% indicated absence of coronavirus disease 2019 pretesting. Most (83%) operators expressed concern when asked to perform cardiac catheterization on a suspected or confirmed coronavirus disease 2019 patient, primarily because of fear of viral transmission (88%). Although the survey demonstrated significant compliance with social distancing, high use of telemedicine (69%), and online education platforms (80%), there was concern over impending financial loss. CONCLUSIONS: Our survey indicates significant reduction in invasive procedure volumes and concern for viral transmission. There is near universal adoption of personal protective equipment; however, coronavirus disease 2019 pretesting and access to FIT‐tested N95 masks is suboptimal. Although there is concern over impending financial loss, substantial engagement in telemedicine and online education is reported.